Efek Perendaman Biji dalam PGPR terhadap Pertumbuhan Semai Cabai Rawit (Capsicum frutescens L.) - Hesti Kurniahu (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic))
The process of cayenne pepper seedling begins with soaking the seeds in liquid to break the dormancy of the seeds. The effect of soaking cayenne pepper seeds using PGPR solution obtained from the root system of cultivated plants, namely cayenne pepper (Capsicum frutescens L.), maize (Zea mays L.), peanuts (Arachys hypogaea L.), and rice (Oryza sativa L.) which had been harvested was the purpose of this study. Cayenne pepper seeds were soaked overnight using PGPR, then the seeds were sown in a planting medium mixed with soil, manure, compost and husk charcoal in a ratio of 2:1:1:1. Cayenne pepper seedling plantations were observed for 4 WAP. Using one-way ANOVA test for research data. Soaking cayenne pepper seeds using PGPR had a significant effect on seedling growth in terms of height, number of leaves, and stem diameter parameters with optimal treatment of 50% concentration. Meanwhile, PGPR immersion for seedling root length parameters did not have a significant effect.